2021
DOI: 10.1002/mrm.28967
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance conditionality of abandoned leads from active implantable medical devices at 1.5 T

Abstract: During MR scans, abandoned leads from active implantable medical devices (AIMDs) can experience excessive heating at the lead tip, depending on the type of termination applied to the proximal contacts (proximal end treatment). The influence of different proximal end treatments (ie, [1] freely exposed in the tissue, [2] terminated with metal in contact with the tissue, or [3] capped with plastic, and thereby fully insulated, on the RF-induced lead-tip heating) are studied. A technique to ensure that MR Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Since MR-Conditional labeling of a CIED only applies to the intact device with leads implanted in their original configuration, patients with abandoned leads are contraindicated for MRI. A recent study showed that capped abandoned leads induce tissue heating that is on average 3.5 times higher than what is generated by a complete CIED system (40). Thus, results of this study should not be generalized to cases of abandoned leads.…”
Section: Discussionmentioning
confidence: 99%
“…Since MR-Conditional labeling of a CIED only applies to the intact device with leads implanted in their original configuration, patients with abandoned leads are contraindicated for MRI. A recent study showed that capped abandoned leads induce tissue heating that is on average 3.5 times higher than what is generated by a complete CIED system (40). Thus, results of this study should not be generalized to cases of abandoned leads.…”
Section: Discussionmentioning
confidence: 99%
“…There are 49 landmarks for each human body model using a 25‐mm step size to cover the imaging of the head region down to the foot/ankle region. Two different generic RF coils are used in the simulations 17 . The larger coil used for adult obese male simulations has a length of 650 mm, a diameter of 700 mm, and 16 rungs.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, in ISO/TS 10974, a more efficient transfer function (TF) method is proposed and utilized to assess the RF‐induced heating for AIMD systems. Combined with clinically relevant incident electric fields along possible implantation pathways inside human body models or inside the American Society for Testing and Materials (ASTM) phantom, the TF method can quickly numerically predict the RF‐induced heating for both inside human body models and in vitro scenarios 17–20 …”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence to help quantify the risks of abandoned or fractured transvenous permanent pacemaker and defibrillator leads is mixed with some studies suggesting large temperature increases both in vitro56 57 and in vivo animal studies 58. More recently, in vitro testing at 1.5 T has demonstrated greater MRI-induced heating in abandoned leads (up to 29.9°C) compared with pacemaker-connected leads (up to 11.6°C),59 60 although temperature rises were strongly dependent on lead length and were generally higher when the abandoned leads were capped.…”
Section: Mr Unlabelled Cied Systems and Mr Conditional Cieds Not Fulf...mentioning
confidence: 99%